A CASE STUDY IN LOSARI DISTRICT, BREBES REGENCY: A LEGAL EXAMINATION OF THE AMENDMENT TO VILLAGE LAW NO. 3 OF 2024 ARTICLE 39 ON THE PERFORMANCE OF VILLAGE HEADS AND VILLAGE SECRETARIES - Roso, Karno; Zainudin, Muhamad; Sulaiman, King Faisal; Kusumaningsih, Gendrik; Kautsar, Muhammad Habib Rizqi (International Journal of Cultural and Social Science, 2026)
The amendment to Law Number 6 of 2014 thru Law Number 3 of 2024, particularly Article 39, brings significant changes to the governance of village administration in Indonesia. This revision extends the term of office for the Village Head from six to eight years and strengthens the administrative role of the Village Secretary. This research examines the legal and empirical implications of these changes for village governance in Losari District, Brebes Regency, which is a border area and considered underdeveloped. Using a legal-empirical approach, data was obtained thru interviews, observation, and document analysis. The research results indicate that the cooperation between the Village Head and the Village Secretary generally supports administrative order and the improvement of public services. However, there are practical challenges such as limited human resources, a decrease in village funds each year, an administrative burden centered on the Village Secretary, the tendency of the Village Consultative Body (BPD) to be passive, and inconsistent public services. The community also demands greater transparency thru information boards and more structured village office management. Despite these challenges, the Village Device Working Team (TIRAKAT) emerged as a local innovation that strengthens adaptive governance. The Village Secretary remains a key figure in maintaining reporting and accountability, with the support of the District Head's oversight function. This research recommends a biennial participatory evaluation, strengthening the capacity of village officials, optimizing the role of TIRAKAT, and digitalization.